Initial agronomic evaluation of Parkia biglobosa in the humid zone of Nigeria - Sabiiti, E.N.; Cobbina, J. (Springer, 1992)
Determines the effect of management regimes (cutting frequency and height) on the coppicing ability, fodder production and nutritive value potentials of cultivated Parkia trees compared with Gliricidia. The study has shown that the tree has a potential as fodder for livestock as well as human food. Examines effect of 8-weekly cutting on leaf and total biomass (kg/ha), effect of cutting interval on coppice productivity, and crude protein, in vitro dry matter digestibility, neutral detergent fibre and tannins of Parkia biglobosa and Gliricidia sepium in the humid zone of Nigeria.